Fela Kuti: contracultura e (con)tradição na música popular africana - Silva, Rosa Aparecida do Couto [UNESP] (2015)
The 60's of the last century is recognized as a period of great countercultural movement. The struggle for civil rights realized mainly by the black people is one of the most important faces of this counterculture, which takes place in the United States and other parts of the world. The Nigerian musician Fela Kuti is strongly influenced by jazz and by the black movement, he creates a musical style called Afrobeat and a whole countercultural scene in Nigeria during the 70's. The work of this musician will be analised through its internal contradictions which, according to our understand, spring from his unique way of understanding the issues that were placed at his time, and his singular way of understanding the role of African culture in the world